Simultaneous determination of the styrene unit content and assessment of molecular weight of triblock copolymers in adhesives by a size exclusion chromatography method. Issue 20 (7th September 2017) - Wang, Mingfang; Wang, Yuerong; Luo, Pei; Zhang, Hongyang; Zhang, Min; Hu, Ping
Abstract: The content of styrene units in nonhydrogenated and hydrogenated styrene‐butadiene‐styrene and styrene‐isoprene‐styrene triblock copolymers significantly influences product performance. A size exclusion chromatography method was developed to determine the average styrene content of triblock copolymers blended with tackifier in adhesives. A complete separation of the triblock copolymer from the other additives was realized with size exclusion chromatography. The peak area ratio of the UV and refraction index signals of the copolymers at the same effective elution volume was correlated to the average styrene unit content using nuclear magnetic resonance spectroscopy with commercial copolymers as standards. The obtained calibration curves showed good linearity for both the hydrogenated and nonhydrogenated styrene‐butadiene‐styrene and styrene‐isoprene‐styrene triblock copolymers ( r  = 0.974 for styrene contents of 19.3–46.3% for nonhydrogenated ones and r  = 0.970 for the styrene contents of 23–58.2% for hydrogenated ones). For copolymer blends, the developed method provided more accurate average styrene unit contents than nuclear magnetic resonance spectroscopy provided. These results were validated using two known copolymer blends consisting of either styrene‐isoprene‐styrene or hydrogenated styrene‐butadiene‐styrene and a hydrocarbon tackifying resin as well as an unknown adhesive with styrene‐butadiene‐styrene and an aromatic tackifying resin. The methodology can be readily applied to styrene‐containing polymers in blends such as poly(acrylonitrile‐butadiene styrene).